Fatal Course of a Male Newborn with Double Duodenal Atresia - Elrouby, Ahmed; Koraitim, Ahmed (European Journal of Pediatric Surgery Reports, 2020)
Multiple point duodenal atresia is an extremely rare condition with atretic segments in either two or three sites of the duodenum. We report a newborn male patient who presented to our institution with bilious vomiting, nonpassage of meconium, mild abdominal distension, and a palpable epigastric abdominal mass ∼1 × 1 cm. A faint double bubble was found on abdominal X-ray. On exploratory laparotomy, a duodenal cyst due to double duodenal atresia was found and a typical diamond-shaped duodeno-duodenostomy was created. A postoperative contrast study revealed passage of the contrast media into distal intestine. However, the patient died 2 weeks later due to uncontrolled sepsis and pneumonia. Despite the fact that multiple-point duodenal atresia is a rare condition, it should be considered as a differential diagnosis to avoid missed pathology.
Keywords: double; duodenum; atresia; abdominal cyst